Gossypiboma: A Cause of Iatrogenic Fecal Enterocutaneous Fistula (Anwer Khan Modern Medical College Journal, 2023)
The word ‘gossypiboma’ or ‘textiloma’ is used to describe a retained surgical sponge in the body after an operation. If it is left in the abdomen, it may cause serious morbidity and mortality of the patient as well as medico legal problems. It varies between 1 out of 1000-1500 intra-abdominal operations and 1 out of 300-1000 of all operations1. Herein, we report one case, the first presenting about 2 months after caesarean section with fever with chills and rigor and pain at the operative area. Imaging detected presence of foreign body in the abdomen. Then she went for exploration of the wound and a mop was removed. After that she came to us with pain and feculent discharge from the wound site.AKMMC J 2021; 12(1) : 58-61